Altering the balance between bacterial production and protistan bacterivory triggers shifts in freshwater bacterial community composition - Simek, Karel; Nedoma, Jirí; Pernthaler, Jakob; Posch, Thomas; Dolan, John R (Antonie van Leeuwenhoek, 2002)
Bacterivorous protists are known to induce changes in bacterial community composition (BCC). We hypothesized that changes in BCC could be related quantitatively to a measure of grazing: the ratio of bacterial mortality to growth rate. To test this hypothesis, we analyzed time-course changes in BCC, protistan grazing rate, and bacterial production from 3 in situ studies conducted in a freshwater reservoir and three laboratory studies. In the field experiments, samples were manipulated to yield different levels of protistan bacterivory and incubated in dialysis bags. Laboratory investigations were continuous cultivation studies in which different bacterivorous protists were added to bacterial communities. BCC was assessed using 4-6 different rRNA-targeted oligonucleotide probes for community analysis. Change in BCC (delta BCC) was estimated as the sum of changes in the proportions of the two phylogenetic groups that showed the largest shifts. Analysis of a set of 22 estimates of shifts in the ratio of grazing to production rate over periods of 48-72 h and A BCC showed that delta BCC was positively and tightly correlated (r2 = 0.784) with shifts in the ratio of grazing mortality to cell production. While the nature of a shift in BCC is unpredictable, the magnitude of the change can be related to changes in the balance between bacterial production and protistan grazing. bacterial community composition
Keywords: Animals; ekosystém; Fresh Water; stravovací zvyklosti; Ecosystem; hybridizace in situ fluorescenční; zvířata; In Situ Hybridization, Fluorescence; kultivační média; Feeding Behavior; Bacteria; Ciliophora; sladká voda; Culture Media; Eukaryota